Spiritual Leadership and Mental Wellbeing: The Role of Kiai in Maintaining Santri Mental Health - Attarwiyah, Nadiatul Maziyyah; Chotib, Moch.; Subakri, Subakri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study explores the managerial role of the Kiai in maintaining the mental health of santri at Pondok Pesantren Al-Qodiri 02, an institution known for integrating religious teachings with psychological support. Using a qualitative case study approach, data was collected through in-depth interviews, participatory observation, and document analysis over six months. The findings reveal that the Kiai enhances santri's mental health by offering emotional connections and spiritual guidance and fostering a nurturing environment. The Kiai also serves as a role model, teaching values such as patience, perseverance, and devotion to Allah, which promote psychological resilience and character development. However, the study’s focus on a single pesantren limits its generalizability to other institutions with different leadership structures and cultural dynamics. Additionally, the reliance on qualitative data may not capture broader trends in mental health across pesantren. The study emphasizes the need for pesantren administrators to create a supportive ecosystem that strengthens Kiai's role in fostering mental well-being and equips santri with life skills for challenges beyond the pesantren setting.